The Mutual Relation in the Effective Cooperation between Natural Environment and Pupils’ Attitude to it in the Creative Heritage of V. Sukhomlynskyi - KotlіarchukНalyna (Pedagogical Discourse, 2016)
Pedagogical experience of V. Sukhomlynskyi in achieving the nature’s potential used for solving problems of modern education process acquires the special actuality on the modern stage of development of humanity. The aim of the article is to expose the basic ideas of V. Sukhomlynskyi on effective organization of co-operating with nature the general school’s students with the aim of education in them of careful attitude toward nature. According to V. Sukhomlynskyi, nature is the determinative factor of self-realization student’s personality and it effectively promotes him to harmonious development. For effective realization of educator potential of natural environment he organized school outdoors, one that got the name «School of happiness». In the unusual educational establishment, he organized lessons in nature’s lap, walks with students to the forest, in the field, on meadows. In turn, intermingling with nature, in opinion of V. Sukhomlynskyi, is one of the fixed assets of forming the high moral qualities of personality in the process of which it learns to see and understand beauty of environment. Therefore, one way to develop in students the careful attitude toward nature, is setting in the class so called «living corner». Close co-operating of students with nature has for an object to teach them not only to see and feel beauty of nature, bring up a mind and teach to talk brightly, accurately and beautifully, but also to bring up the careful, careful landlords of the Earth. Preparation of citizens with the high level of ecological knowledge, ecological consciousness and culture depends on that, how nature is known, as a man sees from little up, understands and feels it, as it is included in their life. Among the forms of realization the educational potential of nature, V. Sukhomlynskyi mostly used excursions in nature, experiments for demonstration of natural processes and phenomena, lessons of thinking and work on nature. Key words: nature, beauty of nature, environment, education, careful attitude.